The state of the art in clinical knowledge management: An inventory of tools and techniques - Sittig, Dean F. (2009)
PURPOSE: To explore the need for, and use of, high-quality, collaborative, clinical knowledge management (CKM) tools and techniques to manage clinical decision support content. METHODS: In order to better understand the current state of the art in CKM, we developed a survey of potential CKM tools and techniques. We conducted an exploratory study by querying a convenience sample of respondents about their use of specific practices in CKM. RESULTS: The following tools and techniques should be priorities in organizations interested in developing successful computer-based provider order entry (CPOE) and clinical decision support (CDS) implementations: 1) A multidisciplinary team responsible for creating and maintaining the clinical content; 2) An external organizational repository of clinical content with web-based viewer that allows anyone in the organization to review it; 3) An online, collaborative, interactive, internet-based tool to facilitate content development; 4) An enterprise-wide tool to maintain the controlled clinical terminology concepts. Even organizations that have been successfully using Computer-based Provider Order Entry with advanced Clinical Decision Support features for well over 15 years are not using all of the CKM tools or practices that we identified. CONCLUSIONS: If we are to further stimulate progress in the area of clinical decision support, we must continue to develop and refine our understanding and use of advanced CKM capabilities.